Improving Content Assessment for English Language Learners: Studies of the Linguistic Modification of Test Items. Issue 2 (24th September 2014) - Young, John W.; King, Teresa C.; Hauck, Maurice Cogan; Ginsburgh, Mitchell; Kotloff, Lauren; Cabrera, Julio; Cavalie, Carlos
Abstract : This article describes two research studies conducted on the linguistic modification of test items from K–12 content assessments. In the first study, 120 linguistically modified test items in mathematics and science taken by fourth and sixth graders were found to have a wide range of outcomes for English language learners (ELLs) and non‐ELLs, with regard to performance on the original and modified versions of the same items. The original items were disclosed items from two states and were used in their standards‐based assessments. The modified versions of these items were developed by a team of Educational Testing Service (ETS) assessment developers and researchers. The ETS research team identified several kinds of modifications that appeared promising and applied the modifications systematically. Ideally, modifying items leads to improved performance by ELLs while having little to no impact on the performance of non‐ELLs. However, both groups of students performed better on some items, about the same on some other items, and worse on yet some other items. Cognitive interviews were conducted as a follow‐up study to investigate which features of the linguistically modified items produced the observed outcomes for ELLs and non‐ELLs. The results from this study added little clarity with regards to which of the linguistic modifications were effective and how they improved the understanding and performance of ELLs on these content items. Abstract : Report Number: ETS RR–14–23